Effects of Diets With Different Protein Levels on Lipid Metabolism and Gut Microbes in the Host of Different Genders - Wang, Kaijun; Peng, Xiaomin; Yang, Anqi; Huang, Yiqin; Tan, Yuxiao; Qian, Yajing; Lv, Feifei; Si, Hongbin (Frontiers in Nutrition, 2022)
The purpose of this experiment was to investigate the effects of different protein levels on lipid metabolism and gut microbes in mice of different genders. A total of 60 mice (30 female and 30 male) were randomly assigned to six groups and fed female mice with low protein diet (FLP), basal protein diet (FBD), and high protein diet (FHP). Similarly, the male mice fed with low protein diet (MLP), basal protein diet (MBD), and high protein diet (MHP). The results of the study showed that both basal and high protein diets significantly reduced the perirenal adipose tissues (PEAT) index in male mice compared to low protein diet (p < 0.05). For the gut, the FHP significantly increased the relative gut weight compared to the FBD and FLP (p < 0.05). At the same time, the FHP also significantly increased the relative gut length compared with the FBD and FLP (p < 0.05). The MHP significantly increased TC concentration compared with the MLP (p < 0.05), and the MBD tended to increase TC concentration compared with the MLP in serum (p =0.084). The histomorphology result of the jejunum and ileum showed that a low protein diet was beneficial to the digestion and absorption of nutrients in the small intestine of mice. While different protein levels had no effect on the total number of fecal microbial species in mice, different protein levels had a significant effect on certain fecal microbes in mice, the absolute abundance of Verrucomicrobia in the feces of male mice was significantly higher in both high and basal protein diets than in the low protein diet (p < 0.05). The high protein diet significantly reduced the absolute abundance of Patescibacteria in the feces of female mice compared to both the basal and low protein diets (p < 0.05). The absolute abundance of Patescibacteria in male feces was not affected by dietary protein levels (p > 0.05). Taken together, our results suggest that a low protein diet can alter fat deposition and lipid metabolism in mice, and that it benefited small intestinal epithelial structure and microbes.